TINJAUAN AWAL KEPERLUAN KAJIAN KEBOLEHPASARAN GRADUAN OKU BERMASALAH PENDENGARAN - Hanapi, Zaliza; Yong, S.S.; Safiee, Zuraifah; Tee, T.K. (Online Journal for TVET Practitioners, 2018)
Every single person on earth has the right to obtain employment that would provide a better quality of life. The hearing impaired must also have this opportunity. As such, this preliminary review has been conducted to study the employability level of hearing impaired graduates amongst the vocational graduates. 96 hearing impaired individuals who are under employment have taken part in the survey by answering the questionnaire given online. The data was analyzed descriptively by using SPSS to obtain the percentages & frequencies. Overall, the preliminary survey came to the conclusion that hearing impaired individuals face employability challenges such as not having compatible acquired skills in connection with current employment, communication difficulties, longer length of time to secure employment and lower monthly salary. At the same time, a focus group interview was also carried out with seven hearing impaired graduates. As a result of these interviews, it is discovered that the hearing impaired face difficulty in the process of seeking employment and are dissatisfied with the different treatment given compared to those who are not handicapped. The hearing impaired have also agreed to develop a employability model that reflects the employability elements that’s specifically designed for them. In conclusion, the employability level of hearing impaired graduates is still unsatisfactory and needs to be improved. Hence, it is imperative to conduct more extensive research into the graduates' employability in terms of employability skills, self-evaluation and discrimination in the work place.